2009
DOI: 10.1007/s00253-009-2271-6
|View full text |Cite
|
Sign up to set email alerts
|

ATP-citrate lyase activity and carotenoid production in batch cultures of Phaffia rhodozyma under nitrogen-limited and nonlimited conditions

Abstract: ATP-citrate lyase (ACL) is the key cytoplasmic enzyme which supplies acetyl-CoA for fatty acids in oleaginous yeast. Although it has been suggested that fatty acid and carotenoid biosynthesis may have a common source of acetyl-CoA in Phaffia rhodozyma, the source for carotenoids is currently unknown. The purpose of this work was to analyze the development of ACL activity during batch cultures of P. rhodozyma under ammonium-limited and nonammonium-limited conditions and study its possible relationship with caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…These data suggested that a certain degree of protein synthesis inhibition could increase astaxanthin production. Therefore, selecting an amino acid-deficient strain through breeding methods [40] or adopting a metabolic regulation method to inhibit protein synthesis [21,22,24] can be an effective method to improve astaxanthin yield. P. rhodozyma is known as a kind of oleaginous yeast and can accumulate a large quantity of lipids [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggested that a certain degree of protein synthesis inhibition could increase astaxanthin production. Therefore, selecting an amino acid-deficient strain through breeding methods [40] or adopting a metabolic regulation method to inhibit protein synthesis [21,22,24] can be an effective method to improve astaxanthin yield. P. rhodozyma is known as a kind of oleaginous yeast and can accumulate a large quantity of lipids [23].…”
Section: Discussionmentioning
confidence: 99%
“…In the process of glucose catabolism, ethanol will be produced during yeast fermentation if dissolved oxygen is insufficient or if glucose concentration is extremely high. Ethanol synthesis could consume the limited carbon source in medium, and previous studies showed that ethanol metabolism during fermentation could be important in astaxanthin synthesis [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Another pathway using a codon-optimized ACS from a facultative anaerobic bacterium (i.e., Salmonella enterica) also led to a dramatic increase of 1-hexadecanol production ( $ 69%) in this study. It has been reported that the activity of ACL increased with the supply of oxygen (Chávez-Cabrera et al, 2010), while the activity of some bacterial ACS enzymes was found to be sensitive to oxygen (Jetten et al, 1989;Seravalli et al, 2002). Since fatty acid biosynthesis in yeast requires oxygen (Fornairon-Bonnefond et al, 2002), we have chosen the aerobic growth condition in this study to produce 1-hexadecanol.…”
Section: The Rate-limiting Steps In Producing Fatty Alcoholmentioning
confidence: 99%
“…1a), when maximum production of carotenoids was achieved, an evidence of the fact that carotenoid synthesis is not directly associated with cell growth of this yeast. Likewise, Chávez-Cabrera et al (11) found that the concentration of total proteins and pigments shows opposing trends, implying that protein synthesis restriction, necessary for cell growth, stimulates carotenoid synthesis by X. dendrorhous. Liu and Wu (30) also observed that carotenoids are synthesized as secondary metabolites Good reproducibility of the carotenoid bioproduction can be verifi ed in trials 13, 14 and 15 (central points) of the Plackett -Burman design (Table 2 and Fig.…”
Section: Carotenoid Production Kineticsmentioning
confidence: 99%
“…Therefore, the yeast Phaffi a rhodozyma (also referred to as Xanthophyllomonas dendrorhous) stands out as a natural source of carotenoids (8)(9)(10)(11)(12) due to its ability to assimilate diff erent carbon sources as substrates, heterotrophic metabolism, relatively fast growth rate, ability to reach high cell density and nutrient quality and safety as a food additive. Besides, it has been certifi ed as a GRAS (Generally Recognized as Safe) microorganism.…”
Section: Introductionmentioning
confidence: 99%